2015
DOI: 10.1016/j.nano.2014.08.009
|View full text |Cite
|
Sign up to set email alerts
|

Efficient nanoparticle-mediated needle-free transcutaneous vaccination via hair follicles requires adjuvantation

Abstract: In vaccine development, activating the immune system is the major challenge. In this perspective, transcutaneous immunization (TCI) offers an attractive approach due to the presence of abundant antigen presenting cells (APCs) such as Langerhans cells and dendritic cells. In particular transfollicular vaccination aims to deliver antigens to the abundant perifollicular APCs without compromising the SC barrier function. The present work clearly demonstrates the potential of transfollicular immunization as an appr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 32 publications
0
27
1
Order By: Relevance
“…The hair follicle provides both a rich pool of peri-follicular APCs and a permeable sites due to the absence of a SC barrier in the lower follicular orifice, facilitating antigen uptake (Figure 4) [20]. Recently, polymeric nanoparticles, smaller than 200 nm, have been found penetrating into the hair follicles and being captured by peri-follicular APCs [2124]. But the skin should be pretreated with cyanoacrylate stripping to reduce the barrier due to the poor skin penetration of polymeric nanoparticles.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The hair follicle provides both a rich pool of peri-follicular APCs and a permeable sites due to the absence of a SC barrier in the lower follicular orifice, facilitating antigen uptake (Figure 4) [20]. Recently, polymeric nanoparticles, smaller than 200 nm, have been found penetrating into the hair follicles and being captured by peri-follicular APCs [2124]. But the skin should be pretreated with cyanoacrylate stripping to reduce the barrier due to the poor skin penetration of polymeric nanoparticles.…”
Section: Resultsmentioning
confidence: 99%
“…However, due to poor dermal permeation into the rigid structure, tape stripping or iontophoresis should be combined to facilitate transdermal delivery [2123, 26]. Besides, adjuvants are necessary to be combined with nanoparticles to generate efficient immune responses [24]. …”
Section: Introductionmentioning
confidence: 99%
“…A 2-phased reaction of skin to barrier disruption has been described [39]. Some authors found a Th2- and eosinophil-focused response after tape stripping as well as increased IgG titters of anti-ovalbumin after application of a correspondent vaccine when applied on tape-stripped skin [38,40,41]. In this context different vaccine formulations might be worth comparing since other findings suggest higher antigen amount distribution to the hair follicle when the compound is encapsulated in nanoparticles [42].…”
Section: Discussionmentioning
confidence: 99%
“…In a relevant mouse model we could recently demonstrate that transfollicular delivery of ovalbumin using polymeric nanoparticles (NPs) may lead to a significant cellular and humoral immune response, without compromising the SC barrier by any pretreatment, provided this nanotechnology approach is combined with some innovative adjuvantation [69][70][71]. This is another example for the potential of nanomedicine to effectively address the immune system (compare with the section 'Nanocarriers interfering with the immune system').…”
Section: Targeting Of Nanomedicines To the Intestinal Mucosa For The mentioning
confidence: 99%